A Microcontroller-based guiding system using infrared and ultrasonic sensors for the blind - Bantayan, Lawrence Matthew J. (Animo Repository, 2009)
In the past leading up to today, various types of electronic devices have been made for the blind. Some of the notable types include Braille-based devices, guiding and alerting devices for walking, and GPS navigation systems. However, the current innovation trend shows more focus and developments are being given to Braille-based devices and less concern are given in the development and improvement of guiding devices for the blind to walk safely. In this thesis, an improved guiding system is developed with the use of a microcontroller, infrared distance measuring sensors, ultrasonic ranging sensors, and vibrating motors. The guiding system provides capabilities to detect and discern different types of path obstructions that other existing systems do not have. These path obstructions include: (1) small obstacles, (2) walls, (3) low-level beam/ceiling, and (4) upward sloping stairways (National Building Code measurement standard). The prototype has four main subsystems: (1) the walking stick, which holds three infrared distance measuring sensors and two ultrasonic ranging sensors for detecting path obstructions at the lower body level, (2) the hat, which holds an infrared distance measuring sensor for detecting low-level beams/ceilings that could hit the user on the head, (3) glove, which contains five vibrating motors for alerting the user of the type of path obstruction and its relative distance from the stick/hat, and (4) circuit box, which contains the intelligence of the system through a microcontroller that process the signals coming from the sensors and producing the necessary control signals to the vibrating motors for alerting the user. An actual system test with ten (10) blind people resulted to an overall system performance rating of 7.8/10. Through actual blind user surveys, the device showed great potential in serving as a desirable alternative to the conventional cane being widely used by the blind.